Optimization of process parameters for fabrication of electrospun nanofibers containing neomycin sulfate and Malva sylvestris extract for a better diabetic wound healing - Mohammed Monirul Islam; Varshini Hemmanahalli Ramesh; Penmetsa Durga Bhavani; Prakash S. Goudanavar; N. Raghavendra Naveen; B. Ramesh; Santosh Fattepur; Predeepkumar Narayanappa Shiroorkar; Mohammed Habeebuddin; Girish Meravanige; Mallikarjun Telsang; Nagaraja Sreeharsha (Taylor & Francis Group, 2022)
Diabetes mellitus is one of the most concerning conditions, and its chronic consequences are almost always accompanied by infection, oxidative stress, and inflammation. Reducing excessive reactive oxygen species and the wound's inflammatory response is a necessary treatment during the acute inflammatory phase of diabetic wound healing. Malva sylvestris extract (MS) containing nanofibers containing neomycin sulfate (NS) were synthesized for this investigation, and their impact on the healing process of diabetic wounds was assessed. Using Design Expert, the electrospinning process for the fabrication of NS nanofibers (NS-NF) was adjusted for applied voltage (X1), the distance between the needle's tip and the collector (X2), and the feed rate (X3) for attaining desired entrapment efficacy [EE] and average nanofiber diameter (ND). The optimal formulation can be prepared with 19.11 kV of voltage, 20 cm of distance, and a flow rate of 0.502 mL/h utilizing the desirability approach. All the selected parameters and responses have their impact on drug delivery from nanofibers. In addition, M. sylvestris extracts have been added into the optimal formulation [MS-NS-NF] and assessed for their surface morphology, tensile strength, water absorption potential, and in vitro drug release studies. The NS and MS delivery from MS-NS-NF has been extended for more than 60 h. M. sylvestris-loaded nanofibers demonstrated superior antibacterial activity compared to plain NS nanofibers. The scaffolds featured a broad aspect and a highly linked porous fibrous network structure. Histomorphometry study and the in vitro scratch assay demonstrate the formulation's efficacy in treating diabetic wound healing. The cells treated with MS-NS-NF in vivo demonstrated that wound dressings successfully reduced both acute and chronic inflammations. To improve the healing of diabetic wounds, MS-NS-NF may be regarded as an appropriate candidate for wound dressing.